Republic of Belarus : Technical Assistance Report-Work of Mission on Development of Potential in Area of Government Finance Statistics. (IMF Staff Country Reports; Country Report ;, 2018)
In coordination with the Republic of Belarus (RB) Ministry of Finance (MF), the latest regular International Monetary Fund (IMF) Statistics Department (STA) mission for providing technical assistance (TA) in the area of government finance statistics (GFS) worked in Minsk November 13-14. That mission's chief objective was to inventory progress in the area of government finance statistics in the Republic of Belarus since the previous mission and to assist the MF in improving the quality of statistical data. Government finance statistics provide a comprehensive conceptual and accounting basis suitable for the analysis and assessment of fiscal policy, especially the performance of any country's general government sector (GGS). One of the biggest pluses of implementing GFS methodology in budgeting is achieving coordination among budgeting, financial reporting and statistics. The use of the same terminology by those engaged in budgeting, reporting and statistics guarantees a common understanding among all interested parties. The comparability of numbers, tables and accounts is substantially enhanced, and productivity and the timeliness of data access are thereby increased.